2023
DOI: 10.1038/s41423-023-01039-4
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage phagocytosis of SARS-CoV-2-infected cells mediates potent plasmacytoid dendritic cell activation

Abstract: Early and strong interferon type I (IFN-I) responses are usually associated with mild COVID-19 disease, whereas persistent or unregulated proinflammatory cytokine responses are associated with severe disease outcomes. Previous work suggested that monocyte-derived macrophages (MDMs) are resistant and unresponsive to SARS-CoV-2 infection. Here, we demonstrate that upon phagocytosis of SARS-CoV-2-infected cells, MDMs are activated and secrete IL-6 and TNF. Importantly, activated MDMs in turn mediate strong activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 66 publications
3
6
0
Order By: Relevance
“…Significantly reduced numbers of pDC were identified in the BA.5+MP group by cellular deconvolution using NanoString expression matrices ( Figure 3 , pDC, Supplementary Table 5 ), consistent with the reduction in M1 macrophages ( 85 ). As might be expected, viral load and pDC abundance showed positive correlations, with pDC abundance lower for the BA.5+MP group across all viral loads ( Figure 3B ).…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Significantly reduced numbers of pDC were identified in the BA.5+MP group by cellular deconvolution using NanoString expression matrices ( Figure 3 , pDC, Supplementary Table 5 ), consistent with the reduction in M1 macrophages ( 85 ). As might be expected, viral load and pDC abundance showed positive correlations, with pDC abundance lower for the BA.5+MP group across all viral loads ( Figure 3B ).…”
Section: Resultssupporting
confidence: 67%
“…MPs were recently reported to inhibit phagocytosis of apoptotic cells (known as efferocytosis) ( 42 ), and a top IPA Diseases and Functions annotation was ‘Phagocytosis’, with a high negative z score ( Figure 3A , Phagocytosis; Supplementary Table 5 ). During infection, macrophages phagocytose SARS-CoV-2-infected cells and are thereby activated, and in turn mediate strong activation of plasmacytoid dendritic cells (pDC) ( 85 ). The reduced phagocytosis is thus consistent with a reduction in activated M1 macrophages identified via a series of annotations ( Figure 3 , M1 macrophages); specifically (i) reduced abundance of polyinosinic:polycytidylic acid (pIC) stimulated macrophages (a stimulus that mimics viral double stranded RNA), (ii) a series of IPA Canonical pathways and Diseases and Functions macrophage annotations with negative z scores, and (iii) GSEAs with negative NES and q<0.05 using M1 macrophage gene sets from Xue at al., 2014 ( 65 ) ( Supplementary Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of the current literature, these results align with previous reports but con ict with others. Indeed, several studies showed that exposure of monocytes/macrophages to SARS-CoV-2 triggered the synthesis of in ammatory cytokines, as we found [63][64][65][66][67][68] , whereas others reported that it did not [69][70][71][72][73] . Most of the studies cited above implicated macrophages differentiated in vitro from monocytes, and may not display the same functional properties as monocytes and macrophages imprinted by the lung tissue.…”
Section: Discussionmentioning
confidence: 82%
“…Nevertheless, many macrophages have shown to be positive for SARS-CoV-2 RNA or protein in vivo [44,45], suggesting an ACE2-independent mechanism of viral entry into macrophages. Recent studies have shown that SARS-CoV-2 can infect host cells via clathrin-mediated endocytosis [46], caveolae-dependent endocytosis [47], phagocytosis [48], and macropinocytosis [12] to initiate an inflammatory cascade.…”
Section: Discussionmentioning
confidence: 99%